A slow, efficient and safe nanoplatform of tailored ZnS QD-mycophenolic acid conjugates for in vitro drug delivery against dengue virus 2 genome replication. Issue 12 (5th November 2020) - Dungdung, Ranjeet; Bayal, Manikanta; Valliyott, Lathika; Unniyampurath, Unnikrishnan; Nair, Swapna S.; Pilankatta, Rajendra
Abstract : The graphical abstract represents the synthesis of size engineered ZnS QDs for conjugating anti-viral drug (MPA) and its safe and effective delivery against cytoplasmically replicating dengue virus 2. Abstract : Dengue is a major health concern causing significant mortality, morbidity and economic loss. The development of anti-dengue viral drugs is challenging due to high toxicity, as well as off-target/side effects. We engineered size tuned ZnS QDs as a platform for the efficient delivery of mycophenolic acid (MPA) against dengue virus serotype 2 (DENV2) to evaluate the drug efficacy and toxicity using the DENV2 sub-genomic replicon system in BHK21 cells. The results indicate that the Selectivity Index 50 (SI50 ) of the ZnS QD-MPA conjugate was two orders higher than that of free MPA with lower cytotoxicity. The effect is attributed to the sustained release of MPA from ZnS QD-MPA. The conjugated MPA caused significant inhibition of the virus at the level of replication and viral protein translation. The study underpins the efficiency of the ZnS QD for the delivery of antiviral drugs against DENV2 with negligible toxicity and side effects.